Magnetic separation method for waste lithium ion battery mixed pole piece
By controlling the mixed pole sheet size and pre-magnetization treatment, combined with the synergistic effect of weak magnetism and strong magnetic separation, we can efficiently separate the positive and negative pole sheets of waste lithium-ion batteries, solving the problems of poor separation effect and many impurities in the prior art, and realizing the separation and regeneration and repair of high-purity pole sheets.
Patent Information
- Application Number
- CN202411885144.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The prior art is difficult to efficiently separate the positive and negative electrode sheets of waste lithium-ion batteries, and the separation of the electrode sheets has many impurities and cannot be used as raw materials for regeneration and repair.
By controlling the scale of the hybrid pole sheet, the magnetic difference between the positive and negative pole sheets is improved by using the pre-magnetization method, and combining the synergy between weak magnetic and strong magnetic separation, the positive and negative pole sheets are efficiently separated.
High-purity separation of positive and negative electrode sheets is achieved, and the crystal phase structure of the positive electrode material in the positive electrode sheet is kept intact and can be directly used as a raw material for regeneration and repair.
Smart Images

Figure CN119702635A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for magnetic separation of mixed pole pieces of waste lithium-ion batteries, and in particular to a process for fine magnetic separation of a mixture of waste battery pole pieces, belonging to the technical field of waste battery recycling. Background Art
[0002] In recent years, with the massive retirement of lithium-ion batteries, it is urgent to carry out the comprehensive recycling of waste lithium-ion batteries. Waste lithium-ion batteries contain a large amount of valuable metals, which is far higher than natural minerals and has huge economic value. At present, the comprehensive recycling and treatment methods of waste lithium-ion batteries mainly include wet comprehensive recycling and physical direct regeneration. Among them, the wet recovery element loss rate is large and the three wastes pollution is high. Although direct regeneration is a recycling method with short process, high resource utilization efficiency and high economic value, it has extremely high requirements for the quality of raw materials. Traditional screening, re-selection and other methods are difficult to provide high-quality raw materials, resulting in poor compatibility of direct regeneration. Based on this, starting from the source, through the high-quality separation of mixed pole pieces of waste lithium-ion batteries, ultra-high purity positive electrode sheet materials and negative electrode sheet materials are obtained, which is expected to provide reliable raw materials for subsequent direct regeneration materials.
[0003] At present, there are some patents that use magnetic separation to separate the positive and negative pole pieces of waste lithium-ion batteries. For example, Chinese patent application CN107492695A uses the magnetic difference between the positive and negative pole pieces to magnetically separate the mixed fragments of positive and negative pole pieces in a magnetic field with a strong induction intensity greater than 9000Gs, and selects the positive pole fragments. The separation rate of the positive and negative poles is relatively high, but the magnetic difference between the positive and negative poles in this method is small, and there is no requirement for the scale of the waste pole pieces, which will cause large pole piece materials to cause serious material entrainment, and small-scale materials to cause serious impurity winding, and there are more impurities in the positive and negative pole pieces obtained by magnetic separation. Chinese patent application CN113083848A discloses a method of converting graphite into carbon dioxide for removal and converting lithium iron phosphate into trivalent lithium iron phosphate and iron oxide and other highly magnetic materials through oxidation calcination to improve the magnetism of the material and achieve efficient separation of pole pieces. However, the crystal phase structure of lithium iron phosphate will change during the oxidation calcination process, and the obtained pole pieces cannot be directly regenerated and repaired.
[0004] Therefore, it is necessary to find a method that can achieve efficient separation of positive and negative electrodes of waste lithium-ion batteries without damaging the crystalline structure of the positive electrode material in the positive electrode, so that the obtained positive and negative electrode sheets can be used as raw materials for regeneration and repair. Summary of the invention
[0005] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for magnetic separation of mixed pole pieces of waste lithium-ion batteries. The method controls the scale of the mixed pole pieces, utilizes the pre-magnetization method to improve the magnetic difference between the positive and negative pole pieces, combines the synergistic effect of weak magnetic separation and strong magnetic separation, and efficiently separates the positive and negative pole pieces. The obtained positive and negative pole pieces have high purity, and the positive electrode material in the positive pole piece maintains the original crystalline phase structure, and can be directly used as a raw material for regeneration and repair.
[0006] In order to achieve the above technical objectives, the present invention provides a method for magnetic separation of mixed pole pieces of waste lithium-ion batteries. According to the method, waste lithium-ion batteries are subjected to mechanical crushing, preliminary magnetic separation, air separation and screening to obtain large-scale positive and negative mixed pole pieces; the large-scale positive and negative mixed pole pieces are subjected to pre-magnetization treatment to enhance the magnetic difference of the pole pieces, and then ultra-high purity positive pole pieces are separated by weak magnetic separation, and positive and negative mixed pole pieces are separated by strong magnetic separation, and the remaining materials are ultra-high purity negative pole pieces.
[0007] The technical solution of the present invention first controls the degree of crushing and screening to obtain large-sized mixed positive and negative pole pieces, which is beneficial to prevent fine materials from causing impurity winding in the subsequent processing process, which seriously affects the purity of magnetic separation. At the same time, the iron shell, electrolyte and diaphragm in the waste lithium-ion batteries can be removed by mechanical crushing, preliminary magnetism and air separation. Secondly, the present invention can increase the magnetic difference between the positive active material (such as lithium iron phosphate, ternary material) and the negative pole piece (graphite) in the positive pole piece through pre-magnetization treatment, which is beneficial to create better conditions for subsequent more accurate magnetic separation, and the crystal phase structure of the positive electrode material will not be damaged in this process, which is conducive to the direct regeneration and repair of the positive and negative pole pieces obtained after separation. In addition, the present invention adopts the combined effect of weak magnetic field and strong magnetic field to achieve weak magnetic separation of ultra-high purity positive electrode sheets with strong magnetism, strong magnetic extraction of finely divided positive electrode sheets with weaker magnetism, positive electrode materials and a small amount of negative electrode sheets mixed in the positive electrode sheets due to folding, winding, etc. during the crushing process. The remaining materials are ultra-high purity negative electrode sheets with no magnetism at all. Different electrode sheet materials can be treated differently to improve the overall processing efficiency and economic value of the materials.
[0008] The inventors have discovered that the present invention must use a combination of weak magnetic and strong magnetic methods. If weak magnetic separation is not used, the mixed pole pieces of the positive and negative poles will be magnetically separated and enter the positive pole pieces, causing the purity of the positive pole pieces to decrease. If only weak magnetic separation is used, ultra-high purity negative pole pieces cannot be obtained.
[0009] As a preferred solution, the waste lithium-ion batteries include at least one of waste lithium iron phosphate batteries, waste ternary batteries, waste lithium cobalt oxide batteries, and waste lithium titanate batteries.
[0010] As a preferred solution, the scale range of the crushed waste lithium-ion battery pole piece is 1 cm 2 ~2cm 2 If the battery pole pieces of the present invention are broken to a small scale, the positive and negative pole pieces will lose powder seriously, and the ultra-fine positive and negative pole pieces are prone to large pole piece entrainment, which affects the purity of the final product; if the broken scale is too large, the positive and negative pole pieces are prone to folding and entrainment during the process, resulting in a reduced recovery rate.
[0011] As a preferred solution, the screening adopts a screening system with an aperture of 50 to 200 meshes. The mesh number of the screening system has little effect on the recovery rate of the pole pieces, but if the aperture of the screening system is too small (i.e. the mesh number is too large), some fine pole pieces will enter the subsequent magnetic separation process, causing serious entrainment of fine impurity components, resulting in the positive pole pieces separated having low purity. If the aperture is too large, some positive and negative pole pieces will be lost, and the recovery rate will decrease.
[0012] As a preferred solution, the pre-magnetization process is as follows: a large-scale positive and negative mixed pole piece is subjected to a 1-15 ms -1 The rate of the pre-magnetization device is 0.5-3.0 T. The transmission rate and magnetic field strength need to be comprehensively controlled during the pre-magnetization process of the present invention. If the rate is too fast or the magnetic field strength is too small, the magnetization of the positive and negative mixed pole pieces will be incomplete, resulting in weak magnetism of the positive pole piece, which is not conducive to the subsequent separation and purification; while if the rate is too slow or the magnetic field strength is too large, although it is conducive to purification, the energy consumption is too large and the economic value is reduced.
[0013] As a preferred solution, the pre-magnetization device includes a transport pipe, a magnetic induction coil and a protective cover from the inside to the outside, the magnetic induction coil is wound around the outside of the transport pipe, and the large-scale positive and negative mixed pole pieces are transported from the inside of the transport pipe during the pre-magnetization treatment. The pre-magnetization device of the present invention adopts electromagnetic magnetization means, an induction coil is installed on the outside of the transport pipe, and a protective cover is further installed to shield the magnetic field from being released. The magnetic field strength is controlled by controlling the power-on process and the current size, so as to achieve the regulation of the magnetic strength, and the magnetic moment of the positive magnetic material on the positive pole piece in the positive and negative mixed pole piece of the present invention is rearranged and the internal structure is adjusted through the effect of the pre-established magnetic field, and finally the magnetic properties of the positive material are greatly increased.
[0014] As a preferred solution, the pre-magnetization magnetic field is any one of a steady-state magnetic field, a pulsed magnetic field and an alternating magnetic field.
[0015] As a preferred solution, the processing conditions of the weak magnetic separation are: the magnetic field strength is 0.1-0.5T, and the number of cycles is 3-6 times. If the magnetic field strength of the weak magnetic separation is small and the number of cycles is small, the recovery rate of the positive pole pieces of the waste lithium-ion batteries will be reduced; if the magnetic field strength of the weak magnetic separation is large and the number of cycles is large, some finely divided positive electrode materials or mixed negative pole pieces will be selected, resulting in a reduction in the purity of the positive pole pieces of the waste lithium-ion batteries.
[0016] As a preferred solution, the processing conditions of the strong magnetic separation are: the magnetic field strength is 1.0-2.0T, and the number of cycles is 2-4 times. The strong magnetic separation of the present invention has a small magnetic field strength and a small number of cycles, which will lead to a decrease in the purity of the negative pole piece of the high-purity waste lithium-ion battery; the strong magnetic separation has a large magnetic field strength and a large number of cycles, which will lead to an increase in the process and energy consumption.
[0017] As a preferred solution, the purity of the ultra-high purity positive electrode sheet is greater than 99.90%, and the purity of the ultra-high purity negative electrode sheet is greater than 98.1%. The positive and negative electrode sheets obtained by the magnetic separation method of the present invention have high purity and can be directly used as raw materials for regeneration and repair.
[0018] As a preferred solution, the material processed by the pre-magnetization treatment is solid or liquid; when it is liquid, water or a low-cost organic solvent is used as a dispersant to improve the dispersibility of the positive and negative electrodes.
[0019] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:
[0020] 1) The method of the present invention controls the size of the mixed pole pieces, utilizes the pre-magnetization method to improve the magnetic difference between the positive and negative pole pieces, and combines the synergistic effect of weak magnetic separation and strong magnetic separation to efficiently separate the positive and negative pole pieces. The obtained positive and negative pole pieces have high purity, and the positive pole piece retains the original crystalline structure, and can be directly used as a raw material for regeneration and repair.
[0021] 2) This method has the characteristics of simple operation, short cycle and high economic benefit.
[0022] 3) The method of the present invention controls the degree of crushing and screening to obtain large-sized positive and negative electrode mixed pole pieces, which is beneficial to prevent problems such as impurity winding caused by fine materials in subsequent processing, which seriously affects the purity of magnetic separation.
[0023] 4) The pre-magnetization device used in the present invention has a simple structure and can significantly increase the magnetism of the positive electrode material without destroying the crystalline structure of the positive electrode material through electromagnetic magnetization, thereby facilitating subsequent magnetic separation. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a process flow chart of the present invention.
[0025] Figure 2 This is a schematic structural diagram of the pre-magnetization device used in the present invention.
[0026] Figure 3 This is the XRD of the lithium iron phosphate separated in Example 5 of the present invention. DETAILED DESCRIPTION
[0027] In order to further illustrate the present invention, the contents of the present invention are described in detail below in conjunction with the examples. However, it should be understood that these examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. The protection scope of the present invention is not limited to the following examples.
[0028] The structural schematic diagram of the pre-magnetization device used in the embodiment of the present invention is as follows Figure 2 As shown, from the inside to the outside, it includes a transport pipe, a magnetic induction coil and a protective cover. The magnetic induction coil is wound around the outside of the transport pipe. During the pre-magnetization treatment, large-scale positive and negative mixed pole pieces are transported from the inside of the transport pipe.
[0029] The positive electrode materials remaining in the mixed materials referred to in the embodiments are finely divided positive electrode materials and positive electrode plates with weaker magnetism, and the negative electrode materials are mixed negative electrode plates.
[0030] Example 1 (Comparative Example)
[0031] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 0.1mm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixed materials. The obtained positive and negative electrode mixed materials are passed through a 100-mesh screening system, and the upper layer of materials is high-purity large-scale waste battery large-sized materials. They are passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1, the magnetic field strength transmitted is 1.5T, the magnetic field type adopts a steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.30T, the number of cycles is 4, and ultra-high purity positive electrode pieces are obtained; the remaining material is passed through a strong magnetic separator, the magnetic separation strength is 1.5T, the number of cycles is 3, and finally ultra-high purity negative electrode pieces are obtained. The calculation rule is based on the material after the positive and negative electrode pieces are screened, among which the recovery rate of ultra-high purity positive electrode pieces is as high as 90%, the content of positive electrode materials remaining in the mixed materials is 10%, and the negative electrode materials are 5%, and the recovery rate of ultra-high purity negative electrode pieces is as high as 95%. However, due to the crushing of relatively fine materials in this process, a large amount of positive electrode powder falls off, and the overall recovery efficiency is low. This is mainly because after the materials are crushed into ultrafine powder, some positive and negative electrode materials will fall off from the current collector. After passing through the screening system, the mixed powder will be gathered together to form positive and negative electrode mixed powder. At the same time, after the positive electrode sheet is detached, only aluminum foil is left. The aluminum foil cannot be pre-magnetized and will directly enter the negative electrode system, resulting in a high impurity content in the final material.
[0032] Example 2 (Comparative Example)
[0033] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1cm 2 The large-sized waste battery materials are subjected to magnetic separation, sorting and other processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed pole piece. The large-scale positive and negative electrode mixed pole pieces are initially separated by a weak magnetic separator with a magnetic field strength of 0.30T and 4 cycles to obtain positive pole pieces; the remaining materials are passed through a strong magnetic separator with a magnetic separation strength of 1.5T and 3 cycles to finally obtain negative pole pieces. The calculation rule is based on the materials after screening of the positive and negative electrode pieces, among which the recovery rate of the positive pole pieces is as high as 30%, the content of positive electrode materials remaining in the mixed materials is 70%, and the negative electrode materials are 55%, and the recovery rate of the negative pole pieces is as high as 45%. For the positive and negative electrode mixed pole pieces that have not been pre-magnetized, the magnetic difference between the positive and negative poles is small, and it is difficult to separate them efficiently.
[0034] Example 3 (Comparative Example)
[0035] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1cm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1, the magnetic field strength transmitted is 1.5T, the magnetic field type adopts a steady-state magnetic field, and the material form is solid; the mixed pole piece is passed through a strong magnetic separator, the magnetic separation strength is 1.5T, the number of cycles is 3, and finally the negative pole piece is obtained. The calculation rule is based on the material after the positive and negative pole pieces are screened, where the recovery rate of the positive pole piece is as high as 40%, the positive material content remaining in the mixed material is 60%, and the negative material is 43%, and the recovery rate of the negative pole piece is as high as 57%. If the weak magnetic separation stage is not added, the mixed pole pieces of positive and negative poles will be entrained and separated by magnetic separation into the positive pole piece, resulting in some negative pole pieces being mixed in the positive pole piece material.
[0036] Example 4 (Comparative Example)
[0037] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1mm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1 The magnetic field strength transmitted is 1.5T, the magnetic field type adopts a steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.30T, the number of cycles is 4, and ultra-high purity positive electrode sheets are obtained; the positive and negative electrode sheets are screened as the calculation rule, and the recovery rate of ultra-high purity positive electrode sheets is 80%. The remaining separated negative electrode sheets contain the remaining 20% of positive electrode materials. If high-quality utilization is required, high-acid wet leaching is still required.
[0038] Example 5
[0039] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1mm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1, the magnetic field strength transmitted is 1.5T, the magnetic field type adopts steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.30T, the number of cycles is 4, and ultra-high purity positive electrode pieces are obtained; the remaining material is passed through a strong magnetic separator, the magnetic separation strength is 1.5T, the number of cycles is 3, and finally ultra-high purity negative electrode pieces are obtained. The calculation rule is based on the material after the positive and negative electrode pieces are screened, among which the recovery rate of ultra-high purity positive electrode pieces is as high as 80%, the content of positive electrode materials remaining in the mixed materials is 20%, and the negative electrode materials are 25%, and the recovery rate of ultra-high purity negative electrode pieces is as high as 75%.
[0040] Example 6
[0041] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 2cm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1 , the magnetic field strength transmitted is 1.5T, the magnetic field type adopts steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.30T, the number of cycles is 4, and ultra-high purity positive electrode pieces are obtained; the remaining material is passed through a strong magnetic separator, the magnetic separation strength is 1.5T, the number of cycles is 3, and finally ultra-high purity negative electrode pieces are obtained. The calculation rule is based on the material after the positive and negative electrode pieces are screened, among which the recovery rate of ultra-high purity positive electrode pieces is as high as 75%, the content of positive electrode materials remaining in the mixed materials is 25%, and the negative electrode materials are 18%, and the recovery rate of ultra-high purity negative electrode pieces is as high as 82%.
[0042] Example 7
[0043] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1cm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 50-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1, the magnetic field strength transmitted is 1.5T, the magnetic field type adopts a steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.30T, the number of cycles is 4, and ultra-high purity positive electrode pieces are obtained; the remaining material is passed through a strong magnetic separator, the magnetic separation strength is 1.5T, the number of cycles is 3, and finally ultra-high purity negative electrode pieces are obtained. The calculation rule is based on the material after screening of the positive and negative electrode pieces, among which the recovery rate of ultra-high purity positive electrode pieces is as high as 78%, the content of positive electrode materials remaining in the mixed material is 22%, and the negative electrode material is 26%, and the recovery rate of ultra-high purity negative electrode pieces is as high as 74%. The mesh size of the screen has little effect on the recovery rate of the pieces.
[0044] Example 8
[0045] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1cm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 200-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 1m s -1 , the magnetic field strength transmitted is 1.5T, the magnetic field type adopts steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.30T, the number of cycles is 4, and ultra-high purity positive electrode pieces are obtained; the remaining material is passed through a strong magnetic separator, the magnetic separation strength is 1.5T, the number of cycles is 3, and finally ultra-high purity negative electrode pieces are obtained. The calculation rule is based on the material after the positive and negative electrode pieces are screened, among which the recovery rate of ultra-high purity positive electrode pieces is as high as 81%, the content of positive electrode materials remaining in the mixed materials is 19%, and the negative electrode materials are 22%, and the recovery rate of ultra-high purity negative electrode pieces is as high as 78%.
[0046] The mesh size of the screen has little effect on the recovery rate of the electrode pieces. However, due to the small aperture of the screen, some finely broken electrode pieces enter the subsequent magnetic separation process, causing the entrainment of fine impurity components, resulting in a decrease in the purity of the selected positive electrode pieces.
[0047] Example 9
[0048] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1cm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 15m s -1, the magnetic field strength transmitted is 1.5T, the magnetic field type adopts steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.30T, the number of cycles is 4, and ultra-high purity positive electrode pieces are obtained; the remaining material is passed through a strong magnetic separator, the magnetic separation strength is 1.5T, the number of cycles is 3, and finally ultra-high purity negative electrode pieces are obtained. The calculation rule is based on the material after the positive and negative electrode pieces are screened, among which the recovery rate of ultra-high purity positive electrode pieces is as high as 68%, the content of positive electrode materials remaining in the mixed materials is 32%, and the negative electrode materials are 29%, and the recovery rate of ultra-high purity negative electrode pieces is as high as 71%.
[0049] Example 10
[0050] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1cm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1 , the magnetic field strength transmitted is 0.5T, the magnetic field type adopts steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.30T, the number of cycles is 4, and ultra-high purity positive electrode pieces are obtained; the remaining material is passed through a strong magnetic separator, the magnetic separation strength is 1.5T, the number of cycles is 3, and finally ultra-high purity negative electrode pieces are obtained. The calculation rule is based on the material after the positive and negative electrode pieces are screened, among which the recovery rate of ultra-high purity positive electrode pieces is as high as 55%, the content of positive electrode materials remaining in the mixed materials is 45%, and the negative electrode materials are 35%, and the recovery rate of ultra-high purity negative electrode pieces is as high as 65%.
[0051] Embodiment 11
[0052] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1cm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1, the magnetic field strength transmitted is 3.0T, the magnetic field type adopts steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.30T, the number of cycles is 4, and ultra-high purity positive electrode pieces are obtained; the remaining material is passed through a strong magnetic separator, the magnetic separation strength is 1.5T, the number of cycles is 3, and finally ultra-high purity negative electrode pieces are obtained. The calculation rule is based on the material after the positive and negative electrode pieces are screened, among which the recovery rate of ultra-high purity positive electrode pieces is as high as 78%, the content of positive electrode materials remaining in the mixed materials is 22%, and the negative electrode materials are 33%, and the recovery rate of ultra-high purity negative electrode pieces is as high as 67%.
[0053] Example 12
[0054] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1cm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1 , the magnetic field strength transmitted is 1.5T, the magnetic field type adopts pulse magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.30T, the number of cycles is 3, and ultra-high purity positive electrode pieces are obtained; the remaining material is passed through a strong magnetic separator, the magnetic separation strength is 1.5T, the number of cycles is 3, and finally ultra-high purity negative electrode pieces are obtained. The calculation rule is based on the material after the positive and negative electrode pieces are screened, among which the recovery rate of ultra-high purity positive electrode pieces is as high as 81%, the content of positive electrode materials remaining in the mixed materials is 19%, and the negative electrode materials are 22%, and the recovery rate of ultra-high purity negative electrode pieces is as high as 78%.
[0055] Example 13
[0056] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1cm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1, the magnetic field strength transmitted is 1.5T, the magnetic field type adopts steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.10T, the number of cycles is 3, and ultra-high purity positive electrode pieces are obtained; the remaining material is passed through a strong magnetic separator, the magnetic separation strength is 1.5T, the number of cycles is 3, and finally ultra-high purity negative electrode pieces are obtained. The calculation rule is based on the material after the positive and negative electrode pieces are screened, among which the recovery rate of ultra-high purity positive electrode pieces is as high as 62%, the content of positive electrode materials remaining in the mixed materials is 38%, and the negative electrode materials are 32%, and the recovery rate of ultra-high purity negative electrode pieces is as high as 68%.
[0057] Embodiment 14
[0058] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1cm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1 , the magnetic field strength transmitted is 1.5T, the magnetic field type adopts steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.50T, the number of cycles is 6, and ultra-high purity positive electrode pieces are obtained; the remaining material is passed through a strong magnetic separator, the magnetic separation strength is 1.5T, the number of cycles is 3, and finally ultra-high purity negative electrode pieces are obtained. The calculation rule is based on the material after the positive and negative electrode pieces are screened, among which the recovery rate of ultra-high purity positive electrode pieces is as high as 83%, the content of positive electrode materials remaining in the mixed materials is 17%, and the negative electrode materials are 22%, and the recovery rate of ultra-high purity negative electrode pieces is as high as 78%.
[0059] Embodiment 15
[0060] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1cm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1, the magnetic field strength transmitted is 1.5T, the magnetic field type adopts a steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.30T, the number of cycles is 4, and ultra-high purity positive electrode pieces are obtained; the remaining material is passed through a strong magnetic separator, the magnetic separation strength is 1.0T, the number of cycles is 2, and finally ultra-high purity negative electrode pieces are obtained. The calculation rule is based on the material after screening of the positive and negative electrode pieces, among which the recovery rate of ultra-high purity positive electrode pieces is as high as 80%, the content of positive electrode materials remaining in the mixed materials is 20%, and the negative electrode materials are 17%, and the recovery rate of ultra-high purity negative electrode pieces is as high as 83%. However, the purity of ultra-high purity negative electrode pieces decreases.
[0061] Example 16
[0062] The waste lithium iron phosphate batteries are mechanically crushed to obtain an area of 1cm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1 , the magnetic field strength transmitted is 1.5T, the magnetic field type adopts steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.30T, the number of cycles is 4, and ultra-high purity positive electrode pieces are obtained; the remaining material is passed through a strong magnetic separator, the magnetic separation strength is 2.0T, the number of cycles is 4, and finally ultra-high purity negative electrode pieces are obtained. The calculation rule is based on the material after the positive and negative electrode pieces are screened, among which the recovery rate of ultra-high purity positive electrode pieces is as high as 80%, and the content of residual positive electrode materials in the mixed materials is 20%, and the negative electrode materials are 22%, and the recovery rate of ultra-high purity negative electrode pieces is as high as 78%.
[0063] Embodiment 17
[0064] The waste ternary lithium battery is mechanically crushed to obtain an area of 1cm 2 The large-sized waste battery materials are subjected to magnetic separation and sorting processes to obtain positive and negative electrode mixtures. The obtained positive and negative electrode mixtures are passed through a 100-mesh screening system, and the upper material is a high-purity large-scale positive and negative electrode mixed electrode sheet. It is passed through a conveyor belt through a pre-magnetization device, with a transmission rate of 8m s -1, the magnetic field strength transmitted is 1.5T, the magnetic field type adopts a steady-state magnetic field, and the material form is solid; the pre-magnetized material is initially separated by a weak magnetic separator, the magnetic field strength is 0.10T, the number of cycles is 3, and ultra-high purity positive electrode sheets are obtained; the remaining materials are passed through a strong magnetic separator, the magnetic separation strength is 1.5T, the number of cycles is 3, and finally ultra-high purity negative electrode sheets are obtained. The calculation rule is based on the materials after screening of positive and negative electrode sheets, among which the recovery rate of ultra-high purity positive electrode sheets is as high as 90%, the content of positive electrode materials remaining in the mixed materials is 10%, and the negative electrode materials are 7.0%, and the recovery rate of ultra-high purity negative electrode sheets is as high as 93%. The magnetic physical difference between the positive electrode sheets of ternary materials and the negative electrode sheets of graphite is large.
[0065] The separation conditions of Examples 1 to 17 are summarized in Table 1 and the separation results are summarized in Table 2.
[0066] Table 1
[0067]
[0068]
[0069] Table 2
[0070]
Claims
1. A method for magnetic separation of mixed pole pieces of waste lithium-ion batteries, characterized in that: The waste lithium-ion batteries are subjected to mechanical crushing, preliminary magnetic separation, air separation and screening to obtain large-scale positive and negative mixed electrode sheets; the large-scale positive and negative mixed electrode sheets are pre-magnetized to enhance the magnetic difference of the electrode sheets, and then the ultra-high purity positive electrode sheets are separated by weak magnetic separation, and the positive and negative mixed electrode sheets are separated by strong magnetic separation, and the remaining materials are ultra-high purity negative electrode sheets.
2. The method for magnetic separation of mixed pole pieces of waste lithium-ion batteries according to claim 1, characterized in that: The waste lithium-ion batteries include at least one of waste lithium iron phosphate batteries, waste ternary batteries, waste lithium cobalt oxide batteries, and waste lithium titanate batteries.
3. The method for magnetic separation of mixed pole pieces of waste lithium-ion batteries according to claim 2, characterized in that: The scale range of the crushed waste lithium-ion battery pole piece is 1 cm 2 ~2cm 2 .
4. A method for magnetic separation of mixed pole pieces of waste lithium-ion batteries according to any one of claims 1 to 3, characterized in that: The screening adopts a screening system with an aperture of 50 to 200 meshes.
5. The method for magnetic separation of mixed pole pieces of waste lithium-ion batteries according to claim 4, characterized in that: The process of the pre-magnetization treatment is: -1 The rate passes through the pre-magnetization device, and the magnetic field strength is 0.5~3.0T.
6. A method for magnetic separation of mixed pole pieces of waste lithium-ion batteries according to claim 1 or 4, characterized in that: The pre-magnetization magnetic field is any one of a steady-state magnetic field, a pulsed magnetic field and an alternating magnetic field; The pre-magnetization device includes a transport pipe, a magnetic induction coil and a protective cover from the inside to the outside. The magnetic induction coil is wound around the outside of the transport pipe. During the pre-magnetization treatment, large-scale positive and negative mixed pole pieces are transported from the inside of the transport pipe.
7. The method for magnetic separation of mixed pole pieces of waste lithium-ion batteries according to claim 1, characterized in that: The processing conditions of the weak magnetic separation are: the magnetic field strength is 0.1-0.5T, and the number of cycles is 3-6 times.
8. The method for magnetic separation of mixed pole pieces of waste lithium-ion batteries according to claim 7, characterized in that: The processing conditions of the strong magnetic separation are: the magnetic field intensity is 1.0-2.0T, and the number of cycles is 2-4 times.
9. A method for magnetic separation of mixed pole pieces of waste lithium-ion batteries according to claim 1, 2, 3, 5, 6, 7 or 8, characterized in that: The purity of the ultra-high purity positive electrode plate is greater than 99.90%, and the purity of the ultra-high purity negative electrode plate is greater than 98.1%.
Citation Information
Patent Citations
Separation method for cathode and anode plates in recovery process of lithium ion batteries
CN107492695A
Pre-magnetization magnetic seed magnetic separation method
CN104624364A
Recycling method of positive electrode material of lithium ion battery
CN106920999A
Method and device for separating positive and negative electrode materials of waste lithium battery
CN111129635A
Sorting and recycling method for positive and negative electrode materials of waste lithium iron phosphate battery
CN113083848A
Cited By
Magnetic iron removal device and iron removal method for lithium battery pole piece
CN120861513A
Magnetic iron removal device and method for lithium battery pole piece
CN120861513B